Sphingosine-1-phosphate, a novel TREM2 ligand, promotes microglial phagocytosis to protect against ischemic brain injury - Tengfei Xue; Juan Ji; Yuqin Sun; Xinxin Huang; Zhenyu Cai; Jin Yang; Wei Guo; Ruobing Guo; Hong Cheng; Xiulan Sun (Elsevier, 2022)
The mechanism of sphingosine-1-phosphate (S1P)-mediated phagocytosis remains unknown. Here, we found that S1P or FTY720 (an analog of S1P) promoted microglial phagocytosis in stroke independent of S1PRs. First, we used computer simulation of molecular docking to predict that S1P might be a ligand for triggering receptor expressed on myeloid cells 2 (TREM2). Next, microscale thermophoresis (MST), surface plasmon resonance (SPR) and liquid chromatography-tandem mass spectrometry (LC-MS/MS) were performed to reveal that S1P was a novel TREM2 ligand. Then, we confirmed the pro-phagocytosis of S1P targeting in Trem2-Dap12 transfected CHO cells and TREM2 knockdown microglia. Point mutation analysis showed that D104 was the critical binding residue. Trem2−/− mice were used to demonstrate the role of S1P-induced phagocytosis targeting on TREM2 in protecting against ischemic brain injury. Finally, further studies revealed that apolipoprotein E (APOE) loaded with S1P was released by microglia and bound to apoptotic neurons via LDL receptor related protein 1B (LRP1B) and thereby induced microglia to phagocytose apoptotic neurons. Overall, the present work reveals for the first time that S1P acts as a novel endogenous ligand of TREM2 to effectively promote microglial phagocytosis. Our findings provide a new lead compound for developing immunomodulator targeting on TREM2.